Extravascular Administration of Factor IX: Potential for Replacement Therapy of Canine and Human Hemophilia B - Liles, Darla; Landen, Charles N; Monroe, Dougald M; Lindley, Celeste M; Read, Marjorie s; Roberts, Harold R; Brinkhous, Kenneth M (Thrombosis and Haemostasis, 1997)
Current therapy for hemophilia B requires large intravenous doses of factor IX (F.IX) given in the clinic or at home. Although home therapy is possible for many patients, it is often complicated by factors such as the lack of good venous access. Very little is known about extravascular routes for administering proteins like F.IX (57 kD) or other vitamin K-dependent procoagulant factors into the circulation. Questions about the absorption rate from extravascular administration as well as plasma recovery and bioavailability have arisen recently with the growing availibility of highly purified procoagulant proteins and increased interest in gene therapy of hemophilia B. Therefore, a group of studies were undertaken to determine the absorption rate, plasma recovery, and bioavailability of high purity, human plasma-derived F.IX concentrates administered via extravascular routes in hemophilia B dogs and in one human hemophilia B subject. Five hemophilia B dogs were given human F.IX via either a subcutaneous (SC), intramuscular (IM), intra- peritoneal (IP) or intravenous (IV) route. In a subsequent study, a single SC administration of human F.IX was compared to an identical IV dose of F.IX in the human hemophilia B subject. All extravascular routes of F.IX administration in both the canine and human gave lower levels of circulating plasma F.IX than the IV route, however all routes resulted in measurable F.IX activity. Of the extravascular routes, the IM injection in the canine resulted in a bioavailibility of 82.8%, while the SC injection resulted in a bioavailability of 63.5%. F.IX reached the plasma compartment by all extravascular routes used, confirming that F.IX can be absorbed extravascularly. The duration of measurable F.IX activity following extravascular administration is prolonged beyond that typically seen with IV administration. These data show that significant levels of F.IX may be obtained via SC injection in canine and ‘ human hemophilia B subjects and further highlight the potential of extravascular routes of administration for future experimental and clinical uses of F.IX and other procoagulant proteins.